Benzimidazole - Kendrekar, Pravin; Adimule, Vinayak (Biochemistry, 2022)
Benzimidazole is a comprehensive survey of the known and new methods of benzimidazole synthesis, the spectral and theoretical aspects of existing benzimidazole derivatives, and the anticancer properties of a new class of benzimidazole derivatives. This book examines aspects and newer mechanisms of benzimidazoles containing heterocyclic moiety. Chapters report on anticancer properties of benzimidazole derivatives, novel methods of synthesis of benzimidazoles, versatile nature of the benzimidazoles, spectral and theoretical studies of benzimidazole derivatives, and medicinal importance and pharmacological aspects of benzimidazole derivatives.